Commodity market reforms : lessons of two decades - Akiyama, T.; World Bank. (Washington, D.C. : World Bank, 2001)
The book discusses reforms in the markwt for cocoa, coffee cotton grains and sugar selectively drawing on cross country experiences to determine what works what does not and why. it is invaluable to policy makers economists, commodity specialists and anyone interested in the structure and operations of agricultural commodity markets in developing countries.
Includes bibliographical references and index.
opc 30/09/16
Loans
Keywords: Produce trade; Privatization; Primary commodities; Africa; Developing countries